Experimental investigation of airflow above waves in a horizontal pipe. (January 2019) - Vollestad, P.; Ayati, A.A.; Angheluta, L.; LaCasce, J.H.; Jensen, A.
Highlights: PIV measurements of the gas flow above waves are analyzed. Conditional averaging enables the separation of wave-coherent flow from the full flow field. At high gas flow rates, vortical structures are shed from the crest and populate the detached shear layer. Below the detached shear layer is a region populated by opposite signed vortices. The separation between these two regions coincides with the critical height. Abstract: We investigate the effect of waves on the airflow in horizontal two-phase pipe flow. Velocity fields in the gaseous phase were acquired by particle image velocimetry (PIV), while interfacial elevation was measured with conductance wave probes. The velocity fields were sampled on a wave-following coordinate system which allows for a decomposition of the velocity field into a mean, wave-coherent and fluctuating component by means of a three-component Reynolds decomposition. Additionally, coherent vortical structures were identified by the swirling strength criterion, and their distribution along the waves is investigated. Results suggest that the interaction between turbulent airflow and propagating waves in a pipe has a number of features reminiscent of wind-wave interaction in open systems. Above waves generated by sufficiently high gas flow rates, there is a distinct region of sheltered airflow, and a lifting of the critical layer on the leeward side of the crest. Streamlines of the phase-averaged flow field show a cat's eye structure located close to the crest in this region. Above waves of moderate steepness, we observe a shear layer that remains adjacent to the wave surface. Above steeper waves and higher gas flow rate, this layer detaches from the surface just downstream of the crest. Shear layer separation above waves is traditionally linked to the onset of wave breaking, and it is interesting to note that the case where we observe a separated shear layer in the phase-averaged vorticity field is in a regime of amplitude saturation. The swirling strength criterion reveals that vortical structures are shed from the interface and populate the detached shear layer above the trough. Below the detached shear layer, there is a region populated by counter-rotating vortices. The critical height coincides with the border between these two regions.